2021
DOI: 10.1029/2020jc016578
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Trends in Dissolved Organic Matter Composition and Its Relation to Sea Ice in the Canada Basin, Arctic Ocean (2007–2017)

Abstract: The Arctic region is undeniably changing, with significant losses in sea ice cover and changing riverine inputs to the Arctic Ocean (Peterson et al., 2006). A record low sea ice extent was reported in September 2012 (D. Perovich et al., 2012) and the summer sea ice has not exceeded or returned to pre-2007 levels yet (Perovich et al., 2019). The rapid reduction of Arctic summer sea ice causes an increase in the amount of light penetrating into the ocean (Nicolaus et al., 2012), enhancing sea-ice melt (Markus et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 71 publications
5
25
0
Order By: Relevance
“…Rather, CDOM variations may be related to internal production by a microbial carbon pump that is more active in the basin area than on the shelf. Microbial-origin CDOM fluorescent components are abundant in basin water [19], with previous studies having found a significant increase in levels of the smallest phytoplankton (picophytoplankton) in the basin area in response to environmental changes [39,40].…”
Section: Shelf-basin Difference In Cdom Concentrationmentioning
confidence: 80%
See 2 more Smart Citations
“…Rather, CDOM variations may be related to internal production by a microbial carbon pump that is more active in the basin area than on the shelf. Microbial-origin CDOM fluorescent components are abundant in basin water [19], with previous studies having found a significant increase in levels of the smallest phytoplankton (picophytoplankton) in the basin area in response to environmental changes [39,40].…”
Section: Shelf-basin Difference In Cdom Concentrationmentioning
confidence: 80%
“…Previous report also found that the subsurface layer of basin area has distinctive enriched terrestrial humic EEM signatures [19]. Fluorescent components C3 and C4 can thus trace the distribution of Pacific water in the western Arctic Ocean.…”
Section: Effects Of Ice Melting and Pacific Inflow On Cdom Fluorescencementioning
confidence: 80%
See 1 more Smart Citation
“…Although bulk DOC concentration provides quantitative information regarding DOC production (or input) and consumption (or loss), previous studies have shown that the seasonal production of bioavailable marine DOC via primary production as well as the influence of riverine DOC is not apparently reflected in bulk DOC distribution in the western Arctic Ocean (e.g., the Chukchi and Beaufort Seas) (e.g., Davis & Benner, 2005; DeFrancesco & Guéguen, 2021; Jung, Son, et al., 2021; Mathis et al., 2007; Shen et al., 2012). For example, Davis and Benner (2005) reported that concentrations of bulk DOC did not exhibit a significant seasonal change in surface water of the Canada Basin, but dissolved amino acids concentrations (indicators of bioavailable DOC) increased by 45% between spring and summer.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably because the elevated production of marine DOC in summer is masked by the concurrently enhanced input of riverine DOC, making the changes in bulk DOC concentrations less discernible during productive seasons (Shen, Fichot, et al., 2016). Furthermore, DeFrancesco and Guéguen (2021) found no interannual variation in bulk DOC concentration in the polar mixed layer of the Canada Basin over an 11‐year period (2007–2017), although the composition of dissolved organic matter (DOM) showed pronounced changes over time. The aforementioned previous studies suggest that the seasonal variations in marine or riverine DOC are reflected in the composition of DOC but less in bulk DOC concentrations.…”
Section: Introductionmentioning
confidence: 99%